Cognitive function. Survey of elderly persons living at home in rural Newfoundland. - Worrall, G. (College of Family Physicians of Canada, 1993)
We tested the cognitive function of elderly, community-dwelling residents in rural Newfoundland using the Canadian Mental Status Questionnaire. The prevalence of moderate and severe cognitive impairment was 9.3%. Physicians in the community had recognized those with severe impairment, but had not recognized any of those with moderate impairment. Cognitive function testing should be part of the periodic health examination of older patients.